Translation of Metaphors Within The Lyrics of Queen’s Songs - Akhmad Fauzan Nugraha; Dimas Adika (PRAGMATICA : Journal of Linguistics and Literature, 2024)
This research is entitled “Translation of Metaphors Within the Lyrics of Queen’s Songs” and was made to identify metaphors contained in several Queen’s songs, furthermore is to find out the meaning contained of the metaphorical lyrics written. Data sources were obtained from Queen’s songs on A Night at the Opera, Queen II, and Jazz albums. Data samples were obtained through the lyrics contained from Queen’s Official YouTube music videos. The theoretical foundation used in compiling this research is the theory of metaphor proposed by Marcella (2017), and Nurgiyantoro (2017) and the theory of translation proposed by Frans Sayogie (2014). The method used in this research is a qualitative method, starting with collecting metaphor samples contained in three different Queen songs from three different albums, then the samples are analyzed to find out the meaning or message contained in each metaphor samples and then translated into Indonesian (TL). The results of this research presented a total of 23 metaphorical sentences, and this study concludes about the importance of translating metaphorical sentences appropriately and acceptably without losing the message contained in the metaphorical sentences, in this case the songwriter uses metaphors to convey the depiction of something based on events and personal experiences of the songwriter.